Exploring linguistic correlates of social anxiety in romantic stories. Issue 5 (2nd September 2016) - Fernandez, Katya C.; Gordon, Elizabeth A.; Rodebaugh, Thomas L.; Heimberg, Richard G.
Abstract: The current study used computerized linguistic analysis of stories about either going on a date or taking a walk down a street to examine linguistic correlates of social anxiety in a sample of undergraduate students. In general, linguistic analysis revealed associations of social anxiety with several linguistic variables, including negative emotion, affect, and anxiety words. Participants higher in social anxiety wrote fewer affect words. The relationship between social anxiety and anxiety words depended on gender, whereas the relationship between social anxiety and negative emotion words depended on both gender and the nature of primes (supraliminal vs. subliminal) received. Overall, our findings highlight the potential utility and benefits of using linguistic analysis as another source of information about how individuals higher in social anxiety process romantic stimuli.